AlCl3 exposure regulates neuronal development by modulating DNA modification - Cheng, Xue-Jun; Guan, Fu-Lai; Li, Qian; Dai, Gong; Li, Hai-Feng; Li, Xue-Kun (World journal of stem cells, 2020)
As the third most abundant element, aluminum is widespread in the environment. Previous studies have shown that aluminum has a neurotoxic effect and its exposure can impair neuronal development and cognitive function.BACKGROUNDAs the third most abundant element, aluminum is widespread in the environment. Previous studies have shown that aluminum has a neurotoxic effect and its exposure can impair neuronal development and cognitive function.To study the effects of aluminum on epigenetic modification in neural stem cells and neurons.AIMTo study the effects of aluminum on epigenetic modification in neural stem cells and neurons.Neural stem cells were isolated from the forebrain of adult mice. Neurons were isolated from the hippocampi tissues of embryonic day 16-18 mice. AlCl3 at 100 and 200 μmol/L was applied to stem cells and neurons.METHODSNeural stem cells were isolated from the forebrain of adult mice. Neurons were isolated from the hippocampi tissues of embryonic day 16-18 mice. AlCl3 at 100 and 200 μmol/L was applied to stem cells and neurons.Aluminum altered the differentiation of adult neural stem cells and caused apoptosis of newborn neurons while having no significant effects on the proliferation of neural stem cells. Aluminum application also significantly inhibited the dendritic development of hippocampal neurons. Mechanistically, aluminum exposure significantly affected the levels of DNA 5-hydroxy-methylcytosine, 5-methylcytosine, and N6-methyladenine in stem cells and neurons.RESULTSAluminum altered the differentiation of adult neural stem cells and caused apoptosis of newborn neurons while having no significant effects on the proliferation of neural stem cells. Aluminum application also significantly inhibited the dendritic development of hippocampal neurons. Mechanistically, aluminum exposure significantly affected the levels of DNA 5-hydroxy-methylcytosine, 5-methylcytosine, and N6-methyladenine in stem cells and neurons.Our findings indicate that aluminum may regulate neuronal development by modulating DNA modifications.CONCLUSIONOur findings indicate that aluminum may regulate neuronal development by modulating DNA modifications.